'I'm more confident now, I was really quiet': exploring the potential benefits of child-led research. Issue 2 (7th February 2017) - Graham, Anne; Simmons, Catharine; Truscott, Julia
Abstract: This article explores whether child-led research (CLR) benefits the well-being of the children and young people involved. The article draws upon evaluation data from a pilot CLR programme facilitated by a non-government organisation that supports disadvantaged children, young people and families. Nine participants (aged 10–14 years old) volunteered for the CLR programme, conducted over 18 weeks, which involved learning about and undertaking their own research on a topic of their choosing. The programme was externally evaluated both in terms of process and outcomes so as to gain insights into what is involved in CLR and any potential benefits it might offer for participants. The discussion explores a range of positive benefits for children whilst also signalling the challenges involved in planning, implementing and evaluating such initiatives, not least of which is the difficulty in scaling up this kind of research, given its resource-intensive nature.